2020
DOI: 10.4103/aam.aam_34_19
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalemic paralysis as an initial presentation of Sjogren syndrome

Abstract: Sjogren syndrome (SS) is a systemic autoimmune disorder with predominant exocrine gland involvement leading to sicca symptoms. Among extraglandular manifestations, renal disease is the most common. Tubular interstitial nephritis and renal tubular acidosis (RTA) are the common presentations. Mild hypokalemia associated with distal RTA is common in SS, however, severe hypokalemia causing paralysis is unusual. We report the case of a 26-year-old female who presented with hypokalemic paralysis. On evaluation, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“… 2 Distal renal tubular acidosis (dRTA) occurs in about 25% of patients with pSS but only 8% of patients with distal renal tubular acidosis also have a prior diagnosis of pSS. 5 , 6 Usually, dRTA presents with mild hypokalemia and normal anion gap acidosis. However, very few cases reporting severe hypokalemia in dRTA leading to muscle paralysis have been published in the literature.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Distal renal tubular acidosis (dRTA) occurs in about 25% of patients with pSS but only 8% of patients with distal renal tubular acidosis also have a prior diagnosis of pSS. 5 , 6 Usually, dRTA presents with mild hypokalemia and normal anion gap acidosis. However, very few cases reporting severe hypokalemia in dRTA leading to muscle paralysis have been published in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Renal involvement is common in SS, usually in the form of tubulointerstitial nephritis. Most cases, however, are either mild or asymptomatic [ 6 ]. dRTA with severe hypokalemia leading to quadriparesis, although rare, has been reported in several case reports as an initial presentation of SS [ 7 - 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two additional case reports with this association were published in 2020, and another study published recently showed a prevalence of 14.81% of DRTA (16 patients) in a cohort of 108 patients with SLE [ 6 , 7 , 8 ]. Generally, the majority of cases with complete DRTA published in literature are diagnosed due to severe symptoms associated with hypokalemia, such as quadriparesis or even respiratory arrest, and therefore, the real prevalence of DRTA associated with autoimmune diseases is difficult to estimate [ 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Therefore, urinary acidification tests are essential in diagnosing those patients who did not develop any symptoms and would otherwise escape undiagnosed.…”
Section: Epidemiology Clinical Presentation and Diagnosismentioning
confidence: 99%